(untitled) (Bangladesh Journal of Pharmacology, 2016)
To investigate the anti-proliferative activity of flavonoids from onion skins, extraction by 50% ethanol (v/v), soxhlet polar fractionation, pH gradient separation, thin-layer chromatography, and recrystallization methods were used to isolate and purify flavonoids from dry onion skins. Anti-proliferative activities of some flavonoids obtained on leukemia K562 cell line were deter-mined by MTT assay. Results showed that flavonoids of onion skins were mainly in form of quercetin, kaempferol, isorhamnetin, apigenin-7-O-?-D-glucopyranoside, quercetin-3-O-?-D-glucopyranoside, kaempferol-7-O-?-D-glucopyranoside and rutin. Quercetin and kaempferol decreased K562 cell viability, and quercetin had stronger effect. However, isorhamnetin and rutin exhibited certain proliferation-promoting effects. It suggests that ortho hydroxyl groups on B ring of onion flavonoids might be the key structural elements of their cytotoxic effects on K562 cells, and hydroxyl groups in position 3 or carbonyl groups in position 4 might be one of the structural effect elements.